Effects of dietary barley inclusion and glucanase supplementation on the production performance, egg quality and digestive functions in laying ducks - Wei Chen (Animal Nutrition, 2021)
This study evaluated the effects of barley inclusion and glucanase supplementation on the productive performance and digestive function in laying ducks. The experiment used a randomized design with a 5 × 2 factorial arrangement of 5 graded levels of barley (0%, 15%, 30%, 45% and 60%) with or without 1.5 g/kg β-1,3-1,4-glucanase (15,000 U/kg). During the experimental period of 120 d, the weight and total number of eggs within each pen were recorded daily, and egg quality was determined every 4 wk. At the end of the experiment, 3 randomly selected ducks within each replicate were sacrificed, then duodenal digesta and jejunal mucosa was collected. Dietary inclusion of barley had no effects on egg production, daily egg mass or FCR, but supplementation with glucanase improved egg production and FCR (P < 0.01). Barley did not affect feed intake of laying ducks, but glucanase tended to increase feed intake (P = 0.09). Neither barley nor β-glucanase had effects on the egg quality variables, except for yolk color score, which was decreased with increasing barley supplementation. Glucanase, but not barley, increased the activity of chymotrypsin and amylase in duodenal digesta. Barley inclusion affected the activity of alkaline phosphatase and maltase in jejunal mucosa (P < 0.05), but β-glucanase had no effects on the activity of these brush border enzymes. Barley inclusion increased the glucan content in duodenal digesta, but supplementation of glucanase to barley-based diet reduced digesta glucan content and reduced total volatile fatty acids and increased the proportion of acetic acid in cecal contents. The results indicate that, without glucanase, the optimal dietary barley level in the diets of laying ducks is about 13% for maximal production performance; glucanase supplementation of the barley diets improved production performance, probably through enhancing digestive function.